A Novel Active Vibration Control Method for Helicopter Fuselages Based on Diffusion Cooperation - Jingliang Li; Yang Lu (International Journal of Aerospace Engineering)
Against the background of low-frequency vibration control for a helicopter fuselage in flight, active control of structural response (ACSR) has been employed for vibration control design. With the increase in control positions in the fuselage, more actuators and error sensors are needed to meet the vibration reduction requirements, forming a large-scale multichannel system. This leads to a rapid increase in the computation amount, causing the control performance of the conventional centralized algorithm main processor to become poor under overload operation. To this end, a novel distributed active vibration control algorithm based on the diffusion cooperative strategy was proposed and explored in this research. The diffusion cooperative strategy is widely used in complex wireless sensor network (WSN) systems to efficiently reduce the computation amount during data aggregation. This distributed algorithm utilizes the advantages of the diffusion-cooperative strategy to reduce the computation amount and coupling relationship of the secondary path in a large-scale multichannel system. First, a novel control law was established by introducing the network topology of the diffusion cooperation strategy into the classical filtered-x least mean square (FxLMS) algorithm, forming the diffusion FxLMS (DFxLMS) algorithm. Then, a secondary path trade-off quantization standard based on the complex undirected network connectivity condition was developed. It determined whether a secondary path was discarded or not and formed the topology of a large-scale multichannel system control network. To examine the effectiveness and superiority of the proposed DFxLMS algorithm, a comparative simulation with a scale of 1 × 10 × 10 was carried out for a simplified helicopter fuselage. Numerical results in realistic scenarios showed the ability of the DFxLMS algorithms to achieve good control performance when proper values of these parameters are chosen.